Inter‐device agreement of sacral subepidermal oedema measurement in healthy adults during prolonged 60° head of bed elevation - Sharon L. Latimer; Madeline Bone; Rachel M. Walker; Lukman Thalib; Brigid M. Gillespie (Wiley, 2024)
Abstract Aim To investigate the level of agreement between the SEM 200 and Provisio® subepidermal moisture sacral delta measurements, which may indicate increased pressure injury risk, in healthy adults during 120 min of prolonged 60° head of bed elevation. This position, which requires the elevation of the patient's upper body at a 60° angle above the horizontal plane for an extended period, is used by clinicians to prevent or manage a patient's medical or surgical conditions. Design This prospective exploratory study recruited 20 healthy adults during October 2021 and collected sacral subepidermal moisture delta measurements using the SEM 200 and Provisio® devices. Methods Delta measurements were taken at 20‐min intervals over 120 min resulting in seven data collection timepoints. Descriptive statistics and a Bland Altman plot analysis were conducted. Results A total of 280 sacral subepidermal moisture delta measurements were gathered or 140 per device. There were good levels of agreement between the two devices at baseline (T0) [mean 0.025; SD 0.137] and following 60‐ (T3) [mean 0.025; SD 0.111], 80‐ (T4) [mean −0.01; SD 0.177] and 100 min (T5) [mean 0.01; SD 0.129] of prolonged 60° head of bed elevation. Head of bed elevations can increase a patient's risk of sacral pressure injuries. In some countries, nurses have access to the SEM 200 and/or the Provisio® device, so our findings may increase nurses' confidence in the interchangeability of the device measurements, although further research is needed to confirm this. The SEM 200 and Provisio® subepidermal moisture scanners show promise in gathering similar objective pressure injury risk data which could prompt clinicians to implement prevention strategies. Impact Current pressure injury risk assessment is largely subjective in nature. This quantitative study on healthy human sacral tissue found a good level of agreement in the SEM 200 and Provisio® subepidermal moisture scanners, which may increase nurses' confidence in the interchangeability of the devices in clinical practice.